Investigating Environmental Degradation of Banana-Sisal Epoxy Composites: Physical and Thermal Properties - Unegbu, Hyginus Chidiebere Onyekachi; YAWAS, Danjuma S.; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Fakultas Teknik, Universitas Lampung, 2025)
This study evaluates the environmental degradation of banana-sisal epoxy composites, focusing on their physical and thermal properties after exposure to moisture, ultraviolet (UV) radiation, and thermal aging. Alkali-treated and untreated composites were fabricated and tested for moisture absorption, tensile strength, flexural strength, thermogravimetric stability, and UV resistance. Results indicate that alkali-treated composites absorbed significantly less moisture (1.26%) than untreated composites (2.62%) after 120 hours of water immersion. Treated composites retained 87.6% of their initial tensile strength and 92% of their flexural strength, demonstrating superior mechanical performance compared to untreated composites. Thermogravimetric analysis (TGA) showed higher onset degradation temperatures (Tonset = 275°C) for treated composites compared to untreated composites (Tonset = 255°C) and better residual mass retention at 600°C. Differential scanning calorimetry (DSC) revealed a higher glass transition temperature (Tg = 93°C) for treated composites, indicating improved thermal stability. After 100 hours of UV exposure, treated composites retained 82% of their tensile strength, compared to 68% for untreated composites. These findings demonstrate that alkali-treated banana-sisal epoxy composites possess enhanced resistance to environmental degradation, making them viable for use in construction, automotive, and marine industries. Future research should aim to optimize fiber treatments, develop hybrid and nanocomposites, and conduct long-term durability and sustainability assessments.